2015
DOI: 10.2147/lra.s91991
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study to correlate breech presentation and enhanced risk of postspinal hypotension during cesarean delivery

Abstract: BackgroundSubarachnoid blockade for cesarean section still poses a threat of profound hypotension and can result in unstable maternal and fetal hemodynamics. The correlation of fetal breech and vertex presentation with the occurrence of hypotension under spinal anesthesia is reviewed in this retrospective, double-blind study.Patients and methodsThe study was conducted on pregnant females scheduled for a lower segment cesarean section between January 2014 and December 2014. After applying inclusion criteria, 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…First of all, post‐spinal hypotension is also influenced by other factors besides anxiety. A previous study has shown that parturients with breech presentation had a higher incidence of post‐spinal hypotension 16 . Neonatal weight, maternal age, and peak sensory block height have also been shown to influence the incidence of post‐spinal hypotension 17 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First of all, post‐spinal hypotension is also influenced by other factors besides anxiety. A previous study has shown that parturients with breech presentation had a higher incidence of post‐spinal hypotension 16 . Neonatal weight, maternal age, and peak sensory block height have also been shown to influence the incidence of post‐spinal hypotension 17 .…”
Section: Discussionmentioning
confidence: 97%
“…A previous study has shown that parturients with breech presentation had a higher incidence of post-spinal hypotension. 16 Neonatal weight, maternal age, and peak sensory block height have also been shown to influence the incidence of post-spinal hypotension. 17 Furthermore, increased pregnancy weight-gain, history of hypotension, baseline systolic blood pressure <120 mm Hg, and a baseline heart rate >100 beats per minute were found to have an influence on the frequency of spinal-hypotension.…”
Section: Discussionmentioning
confidence: 99%